A dielectric study on spark plasma sintered monoclinic HfO2 processed through precursor route - S. S. Lokesh Vendra; Ekaterina Koroleva; Alexey Filimonov; Sergey Vakhrushev; Ravi Kumar (Journal of Advanced Dielectrics)
This work investigated the structure and dielectric behavior of precursor-derived spark plasma sintered (SPS) hafnium dioxide (HfO2). X-ray diffractograms confirmed the presence of monoclinic HfO2 (m-HfO2) and scanning electron micrographs revealed micron/nanosized grains and grain boundaries in SPS m-HfO2. The theoretical density of ceramics is 94%, and the porosity is very low. In the temperature interval of 25–[Formula: see text]C, the real part of the permittivity ([Formula: see text]) is almost frequency- and temperature-independent and the [Formula: see text] value is about 21 in the frequency range 10[Formula: see text]106[Formula: see text]Hz. [Formula: see text] of SPS ceramics is higher than that of traditionally sintered HfO2 ceramics. At temperatures above 225∘C, there is a sharp increase in the permittivity and loss at low measuring frequencies. In order to comprehend the underlying conduction mechanisms, an analysis of the dispersion dependences of the dielectric response was undertaken. High permittivity values were attributed to the space charge polarization mechanism occurring at grain boundaries due to the thermally activated movement of oxygen vacancies. The DC conductivity of SPS m-HfO2 is thermally activated, and conductivity is determined by oxygen vacancies through hopping mechanism.